Analysis of Concept Understanding and Students' Attitudes towards Learning Physics in Material of Straight Motion - Jenny Capriconia; Fatni Mufit (Postgraduate, University of Mataram, 2022)
Understanding the concept and having a positive attitude towards studying physics is a requirement to succeed in studying physics. Studies have shown that students have low conceptual understanding and do not yet have positive attitudes toward learning physics. This research aims to analyze students' conceptual understanding of Straight Motion for class X, analyze students' attitudes towards learning physics, and analyze the correlation between conceptual understanding and students' attitudes towards teaching physics. This type of research is descriptive research with a quantitative approach and the population of all students of class X SMAN in Payakumbuh City and a sample of 205 students. The sampling technique used the purposive sampling technique using the Four-Tier Multiple Choice and Likert Scale. The research results revealed: Students understood the concept of 33.93% in the medium category. Students' attitudes towards studying physics are good, but the indicators of interest in increasing the time to study physics tend to be in the reasonably good category. The correlation between conceptual understanding and student attitudes with a significance value of 0.000 and a correlation value of 0.490 means that the correlation between the concept understanding variable and the student attitude variable is moderate.